Results of the regional nursery for the evaluation of resistance, 1988 - Trutmann, P.; Kayitare, J; Mukishi, P; Ntahimpera, N; Perreaux, D (International Center for Tropical Agriculture, 1988)
Best sources of resistance in the Great Lakes Region were evaluated for stability of resistance and multi-disease resistance at four locations in Burundi, Rwanda and Zaire. Some anthracnose, Angular leaf spot and sources were found resistant at all sites. Correlation analysis also suggest pathogenic variability of Colletotrichum lindemuthianum, Pheoisariopsis griseola, and to a lesser extent for Mycovellosiella phaseoli between sites. ACV8331, G 10747 (late) and G35182 (Phaseolus coccineus subsp polyanthus) had high levels of resistance at all sites tested to anthracnose, angular leaf spot and floury leaf spot. (AS)